Heart Rate Variability during 6-Min Walk Test in Adults Aged 40 Years and Older - Corrêa, F. R.; da Silva Alves, M. A.; Bianchim, M. S.; Crispim de Aquino, A.; Guerra, R.L. F.; Dourado, V. Z. (International Journal of Sports Medicine, 2013)
We evaluated age- and sex-dependent differences in heart rate variability (HRV) during the 6-min walk test (6MWT) in healthy adults. We also evaluated the intensity of the 6MWT based on HRV. 78 participants aged 40–49, 50–59, 60–69, and ≥70 years (42 females; 36 men) performed the 6MWT. Heart rate and HRV were monitored 1 min at rest and during the last 2-min of the test. The root mean square (RMSSD), instantaneous beat-to-beat variability (SD1), and long-term standard deviation (SD2) of RR intervals were calculated. The SD1 <3 ms at the end of the 6MWT was defined as high-intensity exercise. Despite the significantly higher peak values of heart rate observed for women, we did not find sex- and age-related differences in HRV during the 6MWT. The ROC curve identified percentage of maximum heart rate >67% as the best cut-point for prediction of high-intensity exercise with 94% of sensitivity and 65% of specificity (area under the curve=0.804). We may conclude that autonomic modulation of heart rate during exercise was not dependent of age and sex. The HRV assessment during walking enables a valid estimation of exercise intensity in adults. We may therefore suggest the use of 6MWT for assessing exercise capacity and for prescribing exercises in adults aged 40 yrs and older.
Keywords: heart rate variability; walking; exercise